PERAN DAN TUGAS SATUAN POLISI PAMONG PRAJA KABUPATEN KARO DALAM PEMBINAAN DAN PENCEGAHAN PELAJAR YANG TERJARING OPERASI KASIH SAYANG - Soetarto Soetarto; Mia Pepayosa Br Ginting; Aman Ginting Munte (JURNAL GOVERNANCE OPINION, 2021)
The problem of this study is how the role and duties of the Civil Service Police unit in the Guidance and Prevention of Students who are entangled in Affection Operations. The form of research is a descriptive qualitative approach. The research subjects are representatives of the Satpol PP (Pamong Praja Police Unit), parents of students who had been caught in the Affection Operation, and students who had been caught in the Affection Operation. Data collection techniques used are in the form of observation, interviews, and documentation. The results of this study are the role and duties of the Civil Service Police Unit in fostering and preventing students having a positive and major impact on eliminating the number of students who are entangled in Operation Compassion. So it can be concluded that the guidance and prevention carried out by the Civil Service Police Unit includes mental training such as lectures, memorizing Pancasila and the 1945 Constitution and physical training such as push-ups, running to clean the yard and bathroom. The obstacles in carrying out this task are the schedule of raids that are not in accordance with the school curriculum, students who are not aware of their actions and lack of parental attention, resistance from students who are arrested and the displeasure of the owner of the place where the arrests occur.